Studi Komparasi Metode Eksperimen Inkuiri dengan Eksperimen Verifikasi terhadap Hasil Belajar IPA Materi Perpindahan Kalor - Muna, Izza Aliyatul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
This study aims to compare students learning outcomes in the subject of heat transfer using an inquiry experimental method and a verification experiment. The sampleswere PGMI class students which were selected using the purposive sampling technique. The datawere gained from the learning result of the cognitive domain of students obtained from the pre-test and post-test scores which were analyzed by using t-test of two variant equations and psychomotor domain learning result. The students cognitive learning outcome using inquiry learning (N-gain 56.98%) differed significantly higher than that using verification experimental method (N-gain 39.58%). Meanwhile, in term ofpsychomotor aspects covering the skills of assembling tools in practicum, using practicum equipment, performing experiments according to procedures, taking data in practice, and presenting observation, the learning outcomes usinginquiry experimental method and verification experiment were respectively 77.06% and 74.91%. Thus, it revealed that there was no a significant difference between the use of inquiry experimental method and the verification experimental method on psychomotor aspect learning outcomes on the subject of heat transfer.ØØ§ÙÙ ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙØ§Ø±ÙØ© ÙØªØ§Ø¦Ø¬ ØªØ¹ÙÙÙ Ø§ÙØ·ÙØ§Ø¨ ÙÙ ÙØ§Ø¯Ø© Ø§ÙØªÙØ§Ù Ø§ÙØØ±Ø§Ø±Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø·Ø±ÙÙØ© Ø§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙÙØ© ÙØ§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙÙØ©. ÙØ¹ÙÙØ© ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ø§ÙØ·ÙØ§Ø¨ ÙÙ ÙØ³Ù Ø§ÙØªØ±Ø¨ÙØ© ÙÙØ¯Ø±Ø³Ù Ø§ÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ© (Ø£) Ø¨Ø£Ø³ÙÙØ¨ Ø£Ø®Ø° Ø§ÙØ¹ÙÙØ§Øª Ø§ÙÙØªØ¹ÙØ¯Ø© Ø Ø£ÙØ§ Ø¨ÙØ§ÙØ§Øª ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙÙ ÙØªØ§Ø¦Ø¬ Ø§ÙØ·ÙØ§Ø¨ ÙÙØ¬Ø§ÙØ¨ Ø§ÙÙØ¹Ø±ÙÙ ÙØ§ÙØ¬Ø§ÙØ¨ Ø§ÙÙÙØ³ØØ±ÙÙ Ø§ÙÙØØµÙÙØ© Ø¹ÙÙÙØ§ ÙÙ Ø§ÙØ§Ø®ØªØ¨Ø§Ø± Ø§ÙÙØ¨ÙÙ ÙØ§ÙØ§Ø®ØªØ¨Ø§Ø± Ø§ÙØ¨Ø¹Ø¯Ù ÙØªÙØÙÙÙ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§Ø®ØªØ¨Ø§Ø± t ÙÙ Ø§ÙØªØ´Ø§Ø¨Ù ÙÙ Ø§Ø«ÙÙÙ Ø¨ÙÙ Ø§ÙÙØªØºÙÙØ±Ø§Øª. ÙÙØªØ§Ø¦Ø¬ Ø§ÙØªØ¹ÙÙ ÙÙØ¬Ø§ÙØ¨ Ø§ÙÙØ¹Ø±ÙÙ ÙÙ ÙØ§Ø¯Ø© Ø§ÙØªÙØ§Ù Ø§ÙØØ±Ø§Ø±Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø·Ø±ÙÙØ© Ø§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙÙØ© (Â  N-gain 56,98%) ÙÙØ®ØªÙÙÂ  Ø£ÙØ«Ø± ÙÙÙ Ø£Ø¹ÙÙ ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙØ·Ø±ÙÙØ© Ø§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙØ©. (N-gain 39,58%). ÙÙØªØ§Ø¦Ø¬ Ø§ÙØªØ¹ÙÙ ÙÙØ¬Ø§ÙØ¨ Ø§ÙÙÙØ³ØØ±ÙÙ Ø§ÙÙØ´ØªÙÙ Ø¹ÙÙ ÙÙØ§Ø±Ø© ØªÙØ³ÙÙ ÙØªØ¹ÙÙÙ Ø§ÙØ£Ø¯ÙØ§Øª Ø§ÙÙØ³ØªØ®Ø¯ÙØ© ÙÙ Ø¹ÙÙ Ø§ÙÙØ®ØªØ¨Ø±Ø ÙØ§Ø³ØªØ®Ø¯Ø§ÙÙØ§Ø ÙØ§ÙÙÙØ§Ù Ø¨Ø§ÙØªØ¬Ø±Ø¨Ø© Ø·Ø¨ÙØ§ ÙÙØ®Ø·ÙØ§Øª Ø§ÙÙÙØ±Ø±Ø©Ø ÙØ§ØªØ®Ø§Ø° Ø§ÙØ¨ÙØ§ÙØ§Øª ÙÙ Ø¹ÙÙ Ø§ÙÙØ®ØªØ¨Ø±Ø ÙØ¹Ø±Ø¶ ÙØªØ§Ø¦Ø¬ Ø§ÙÙÙØ§ØØ¸Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø·Ø±ÙÙØ© Ø§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙÙØ© (77.06% ) ÙØ§ ÙØ®ØªÙÙ ÙØ«ÙØ±Ø§ Ø¹Ù Ø·Ø±ÙÙØ© Ø§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙØ© (74,91%) . Ø¨ÙØ°Ø§ ÙØ§ ÙÙØ¬Ø¯ ÙØ±Ù ÙØ¨ÙØ± Ø¨ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø·Ø±ÙÙØ© Ø§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙÙØ© ÙØ·Ø±ÙÙØ© Ø§ÙØªØ¬Ø±Ø¨Ø© Ø§ÙØªØÙÙÙØ© ØªØ¬Ø§Ù ÙØªØ§Ø¦Ø¬ Ø§ÙØªØ¹ÙÙ ÙÙ Ø§ÙØ¬Ø§ÙØ¨ Ø§ÙÙÙØ³ØØ±ÙÙ ÙÙ ÙØ§Ø¯Ø© Ø§ÙØªÙØ§Ù Ø§ÙØØ±Ø§Ø±Ø©.